Implementasi Metode SMART Dalam Sistem Pendukung Keputusan Untuk Penentuan Sanksi Tindakan Bullying - Putri, Fetty Ade; Rahman, Maulia; Salsabillah, Tasya (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Bullying is an act that is currently the biggest challenge in Indonesia, especially in schools and Islamic boarding schools. In schools, bullying is usually increasingly rampant because the school does not respond or even ignores violent behavior by its students. Apart from that, giving inappropriate sanctions also causes students who bully to feel safe in carrying out their actions continuously. To be able to provide appropriate sanctions have a deterrent effect, a decision support system is needed that can make it easier for schools to provide sanctions to perpetrators of bullying. By applying the SMART Method, each criterion has a weight that shows how important that criterion is compared to the others. As a result, the system shows that the alternative with alternative code A3 is recommended to receive sanctions in the form of Drop Out because it has a score of 0.800